A nitrogen fix for farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Demand for food is likely to double within the next fifty years but to double yield will require doubling fertilizer availability and, in the case of nitrogen, unless biological nitrogen fixation (BNF) can be improved, a tripling of mineral...